2019
DOI: 10.3762/bjoc.15.129
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Diels–Alder reaction of anthracene by chiral tritylium catalysis

Abstract: The combination of the trityl cation and a chiral weakly coordinating Fe(III)-based bisphosphate anion was used to develop a new type of a highly active carbocation Lewis acid catalyst. The stereocontrol potential of the chiral tritylium ion pair was demonstrated by its application in an enantioselective Diels–Alder reaction of anthracene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Recently, we developed latent carbocation catalysis with chiral phosphate as a counteranion of the trityl cation, which efficiently promoted the asymmetric Friedel–Crafts reaction, HDA reaction, and carbonyl-ene reaction . In addition, we also reported the tritylium salt TrBArF, in situ-generated by Ph 3 CBr and NaBArF-catalyzed redox-neutral α-C­(sp 3 )H arylation of amines and Diels–Alder reaction of β,γ-unsaturated α-ketoesters with anthracenes . In fact, Ph 3 C + -mediated C–H oxidations via a hydride abstraction mechanism are also well-known.…”
mentioning
confidence: 99%
“…Recently, we developed latent carbocation catalysis with chiral phosphate as a counteranion of the trityl cation, which efficiently promoted the asymmetric Friedel–Crafts reaction, HDA reaction, and carbonyl-ene reaction . In addition, we also reported the tritylium salt TrBArF, in situ-generated by Ph 3 CBr and NaBArF-catalyzed redox-neutral α-C­(sp 3 )H arylation of amines and Diels–Alder reaction of β,γ-unsaturated α-ketoesters with anthracenes . In fact, Ph 3 C + -mediated C–H oxidations via a hydride abstraction mechanism are also well-known.…”
mentioning
confidence: 99%
“…Our study can be presented in a broader context. Despite some recent experimental findings, the cascade chirality induction, understood as a sequential induction of helicity in molecular propeller and then in a prochiral substrate, has never been a subject of in-depth studies . Demonstrating the relationship between asymmetric synthesis and dynamic induction of optical activity will confirm the universal nature of the observed phenomena.…”
Section: Discussionmentioning
confidence: 96%
“…The dynamic stereochemistry and residual stereoisomerism of molecular propellers were the subjects of intense studies initiated by Mislow in the early 1970s. Then, after a nearly 20 year period of freezing activity in the field, there was renewed interest in molecular propellers associated with their increasing number of applications. One of the simplest entities showing propensity to residual stereoisomerism, namely, the triphenylmethyl group (CPh 3 , Tr, trityl), is currently used in organic synthesis as protecting devices, catalysts, , construction of molecular machines, medical chemistry, and bioimaging …”
Section: Introductionmentioning
confidence: 99%
“…In 2019, Lv and Luo et al. demonstrated that asymmetric carbocation catalysis with chiral weakly coordinating Fe(III)-based bisphosphate anion was an effective catalytic system for the enantioselective Diels-Alder reactions of β,γ -unsaturated α -ketoesters with unsubstituted anthracene ( Scheme 10 D) ( Zhang et al., 2019a ). It was regarded that the catalytically active chiral ion pair for substrate activation and chiral induction was generated in situ via mixing the Fe(III)-based bisphosphate anion with Ph 3 CCl.…”
Section: Catalytic Asymmetric [2 + N] Annulation Reactionsmentioning
confidence: 99%